Restoring Soil Functions and Agroecosystem Services Through Phytotechnologies - Dessureault-Rompré, Jacynthe (Frontiers in Soil Science, 2022)
Phytotechnology has traditionally been considered as a tool to remediate contaminated soils. While phytotechnology has been generally defined as the application of science and engineering to study problems and provide solutions involving plants, the practical applications go far beyond restoring contaminated land. This review aims to broaden the way we think about phytotechnologies while highlighting how these living technologies can restore, conserve and regenerate the multiple functions and ecosystem services provided by the soil, particularly in the context of agroecosystems. At first, the main problems of soil degradation in agroecosystems are shortly underlined . Subsequently, the importance of plants and their living roots as engines of restoration are reviewed. This paper demonstrates the importance of root traits and functions for soil restoration. It also demonstrates that plant and root diversity together with perenniality are key component of an efficient soil restoration process. Then, a phytotechnology toolbox which includes three pillars for agroecosystems restoration is presented. The three pillars are agricultural practices and land management (1), rhizosphere engineering (2) and ecological intensification (3). This paper also highlights the importance of developing targeted phytotechnology-based restoration strategies developed from root functions and knowledge of rhizosphere processes. More work is needed to evaluate the potential benefits of incorporating phytotechnology-based restoration strategies in the context of grain or vegetable crop productions as most of the studies for agroecosystem restoration strategies were intended to mimic natural prairies.